2019
DOI: 10.1021/acs.orglett.9b04130
|View full text |Cite
|
Sign up to set email alerts
|

Functional Planar Blatter Radical through Pschorr-Type Cyclization

Abstract: A series of functional 2-phenyl-3H-[1,2,4]­triazino­[5,6,1-kl]­phenoxazin-3-yl (planar Blatter) radicals containing CO2Me, CN, and NO2 groups at the C(10) position and 2-phenyl-3H-pyrido­[3,2-b]­[1,2,4]­triazino­[1,4]­benzoxazin-3-yl have been obtained in yields of 40–80% by using the Pschorr-type cyclization and characterized by spectroscopic (ultraviolet–visible and electron paramagnetic resonance), electrochemical, and density functional theory methods. Two of these groups, CO2Me and NO2, have been transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…demonstrated the concept of planar Blatter's radical with the synthesis of several functionalized derivatives of planar Blatter's radical by connecting C(8) and C(10) positions with oxygen and sulphur annulation. [39][40][41] As tabulated in last column of 1 unambiguously confirms the modification in the spin density distribution brought about by X-annulation. The decrease in spin density on ring A and ring B for X-Bl as compared to parent Blatter (Bl) reveals that upon X-annulation, the spin density is drained from ring A and B towards ring C in such a way that it results in a transfer of total 10.5% of spin density from benzotriazinyl core (ring A + ring B) to ring C upon O-annulation.…”
Section: X-annulation In Blatter's Monoradicalsupporting
confidence: 67%
“…demonstrated the concept of planar Blatter's radical with the synthesis of several functionalized derivatives of planar Blatter's radical by connecting C(8) and C(10) positions with oxygen and sulphur annulation. [39][40][41] As tabulated in last column of 1 unambiguously confirms the modification in the spin density distribution brought about by X-annulation. The decrease in spin density on ring A and ring B for X-Bl as compared to parent Blatter (Bl) reveals that upon X-annulation, the spin density is drained from ring A and B towards ring C in such a way that it results in a transfer of total 10.5% of spin density from benzotriazinyl core (ring A + ring B) to ring C upon O-annulation.…”
Section: X-annulation In Blatter's Monoradicalsupporting
confidence: 67%
“…Figure 2 a shows the room‐temperature CW EPR spectrum of the radical precursor dissolved in ethyl acetate, which can be sufficiently well simulated accounting for three 14 N nuclei with isotropic hyperfine interaction (HFI) constants A iso,1 =0.75 mT, A iso,2 = A iso,3 =0.49 mT. Such values agree well with the large amount of studies on various Blatter‐type radicals in solution [45, 55–57] . However, anisotropic values of 14 N HFI constants for Blatter's radicals, which are needed for solid‐state studies, have not been yet reported to the best of our knowledge.…”
Section: Figuresupporting
confidence: 57%
“…Such values agree well with the large amount of studies on various Blatter-type radicals in solution. [45,[55][56][57] However, anisotropic values of 14 N HFI constants for Blatters radicals, which are needed for solid-state studies, have not been yet reported to the best of our knowledge. Figure 2 b shows the X-band (9 GHz) free induction decay (FID)-detected EPR spectrum of a similar radical (used in our previous work, [42] see SI for details) recorded in frozen toluene glass (80 K).…”
Section: Quantumtechnologiesincludingquantumcomputing(qc)mentioning
confidence: 99%
“…27 A much improved yield of 1O-a and access to its functional derivatives were demonstrated with the aza-Pschorr cyclization reaction (Method B). 28–31 Further progress in the synthesis of ring-fused derivatives of 1O-a involved photocyclization (Mallory-type cyclization) of C(8)-substituted benzo[ e ][1,2,4]triazines (Method C, Fig. 1).…”
Section: Introductionmentioning
confidence: 99%